Men’s Attitude Towards Contraception and Sexuality, Women’s Empowerment, and Demand Satisfied for Family Planning in India - Mejía-Guevara, Iván; Cislaghi, Beniamino; Darmstadt, Gary L. (Frontiers in Sociology, 2021)
Whilst the prevalence of unmet need and contraceptive use remained unchanged for ten years (between 2005-2015) in India, gender restrictive norms and power imbalances also have persisted, preventing married women from meeting their family planning desires. Data for this study are from the 2015-6 National Family Household Survey, which contains information on fertility preferences and family planning for women in reproductive age. As a proxy for men’s attitudinal norms, we aggregated men's perceptions regarding contraception (contraception is women's business, women who use contraception may become promiscuous) and control over their wife (if his wife refuses to have sex, men have the right to deny financial support, have sex with another woman, or beat wife) at district level. Using a three-level random intercepts model, we assessed individual and contextual-level associations of men’s attitudinal norms and met need for contraception among sexually active women (aged 15-49) with any demand for family planning, while adjusting for women’s empowerment indicators [education, job status, and adult marriage] and individual demographic factors. Our results indicate that men’s attitudinal norms are negatively associated with women’s contraceptive use; for instance, a 1 standard deviation increase in the proportion of men who believe that contraception is women’s business was associated with a 12% reduced likelihood of contraceptive use (OR=0.88, 95% CI 0.82-0.95). Similar associations remained or were stronger after considering only modern methods, or when excluding female sterilization. Furthermore, our contextual effects analysis revealed that women’s higher education or wealth did not improve contraceptive uptake in communities with strong attitudinal norms, but working women or women married as children were more likely to use contraception in those communities. Our results suggest that men’s attitudinal norms may be dominating over women’s empowerment regarding family planning choices among reproductive age women. However, employment appeared to play a strong protective role associated with women’s contraceptive use. It is important for programs seeking to transform gender equality and empower women in making contraceptive choices to consider women’s employment opportunities and to also address male attitudinal norms in the context of the ecosystem in which men and women coexist and interact.